Intravenous Lidocaine and Ketamine Infusions for Headache Disorders: A Retrospective Cohort Study - Ray, Jason C.; Cheng, Shuli; Tsan, Kirsten; Hussain, Hassan; Stark, Richard J.; Matharu, Manjit S.; Hutton, Elspeth (Frontiers in Neurology, 2022)
1 Abstract 1.1 Introduction The use of lidocaine (lignocaine) and ketamine infusion in the inpatient treatment of patients with headache disorders is supported by small case series. We undertook a retrospective cohort study in order to assess the efficacy, duration and safety of lidocaine and ketamine infusions. 1.2 Methods Patients admitted between 01/01/2018 and 31/07/2021 were identified by ICD code and electronic prescription. Efficacy of infusion was determined by reduction in visual analogue score (VAS), and patient demographics were collected from review of the hospital electronic medical record. 1.3 Results Through the study period, 83 infusions (50 lidocaine, 33 ketamine) were initiated for a headache disorder (77 migraine, 3 NDPH, 2 SUNCT, 1 cluster headache). In migraine, lidocaine infusion achieved a ≥50% reduction in pain in 51.1% over a mean 6.2 days (SD 2.4) . Ketamine infusion was associated with a ≥50% reduction in pain in 34.4% over a mean 5.1 days (SD 1.5). Side effects were observed in 32% and 42.4% respectively. Infusion for medication overuse headache (MOH) led to successful withdrawal of analgesia in 61.1% of lidocaine, and 41.7% of ketamine infusions. 1.4 Conclusion Lidocaine and ketamine infusions are an efficacious inpatient treatment for headache disorders, however associated with prolonged length-of-stay and possible side-effects.